Breast Cancer Genetic Counseling: A Surgeon’s Perspective - Agnese, Doreen M.; Pollock, Raphael E. (Frontiers in Surgery, 2016)
As surgeons who care for patients with breast cancer, the possibility of a cancer diagnosis being related to a hereditary predisposition is always a consideration. Not only are we as surgeons always trying to identify these patients and families, but also we are often asked about a potential hereditary component by the patients and their family members. It is therefore critical that we accurately assess patients to determine who may benefit from genetic testing. Importantly, the potential benefit for identifying a hereditary breast cancer extends beyond the patient to other family members and the risk may not be only for the development of breast cancers, but for other cancers as well. As a surgeon with additional training in clinical cancer genetics, I have perhaps a unique perspective on the issue and feel that a review of some of the more practical considerations is important.